In Vivo Correlation of Radiographic Scoring (Radiographic Union Scale for Tibia Fractures) and Biomechanical Data in a Sheep Osteotomy Model: Can We Define Union Radiographically?. Issue 3 (March 2017) - Litrenta, Jody; Tornetta, Paul; Ricci, William; Sanders, Roy W.; O'Toole, Robert V.; Nascone, Jason W.; Faber, Henry; Wilson, Darren
Abstract : Objective: To determine (1) the reliability of the standard and modified Radiographic Union Scale for Tibia fractures (RUST) score in a sheep osteotomy model, and (2) the standard and modified RUST scores that represent biomechanical union. Design: The tibia cortices in a sheep osteotomy model treated by intramedullary nails were radiographically evaluated using standard and modified RUST scores. Scores that correlated with biomechanical union, based on the torsional stiffness of the contralateral tibia, were determined. Intervention: Two groups of sheep had transverse midshaft osteotomies treated with 10-mm nails after reaming to 11.5 mm. Weight-bearing was allowed as tolerated. Anteroposterior and lateral radiographs were taken at standard intervals from 4 to 12 weeks. The tibial cortices at each time interval were evaluated in a random order by 5 senior orthopaedic trauma surgeons. Each tibia was scored using the standard and modified RUST methods and was assessed for union. Main Outcome Measures: The intraclass correlation coefficient (ICC) was determined for standard and modified RUST scores at each time interval and for the assessment of union. The percentages of fractures that were defined as united by the surgeons were tabulated by RUST and modified RUST scores. The torsional stiffness of each tibia was tested at 12 weeks and expressed as a percentage of the contralateral side. We considered biomechanical union to be ≥90% of the torsional stiffness of the normal side. Results: The modified RUST score demonstrated consistently higher ICCs than the standard RUST. All reviewers considered a standard RUST of 10 and a modified RUST of 14 to represent radiographic union. The standard RUST was 10.4 (range: 8.6–12) and modified RUST was 14.2 (range: 12.2–16) for tibiae that were biomechanically united. Conclusions: The modified RUST score has a slightly higher ICC than the standard RUST. A standard RUST of 10 and a modified RUST of 14 provide an excellent definition of union based on surgeons' opinion and biomechanical testing for a transverse fracture.